Temporal dynamics of antibiotic resistant genes and their association with the bacterial community in a water-sediment mesocosm under selection by 14 antibiotics. (April 2020) - Deng, Chengxun; Liu, Xiaowei; Li, Lanlan; Shi, Jianghong; Guo, Wei; Xue, Jianhui
Graphical abstract: Highlight: Dynamics of ARGs were studied using 120-d operating hydrodynamic mesocosm. Antibiotics had an indirect selective effect on the evolution of ARGs. The propagations and persistence of ARGs was transient. Bacterial community and intI 1 dominated ARG profiles in water and surface sediments. ARGs in deep layer sediments had no correlation with bacterial community and intI 1. Abstract: Antibiotics in aquatic environments at high concentrations and sub-inhibitory concentrations potentially select for the evolution of antibiotic resistant genes (ARGs), posing a potential risk to aquatic ecological safety. Our knowledge of the temporal and successive dynamics of ARGs and bacterial community under the selective pressure of antibiotics in natural water-sediment system was limited. This study used a 120-d operating hydrodynamic mesocosm to explore the temporal dynamics of ARGs in water-sediment systems, and the main selective mechanisms following the attenuation and transport of 14 commonly used antibiotics. Under the selective pressures by antibiotics, ARGs propagated transiently, and persisted after antibiotic removal; the bacterial community structures likewise changed. Mantel test and network analysis indicated that ARGs significantly correlated with the bacterial community in the water and surface sediments. Structural equation model (SEM) further revealed that the evolution of ARGs was mainly due to the direct effect of the change in bacterial community and horizontal gene transfer (HGT) via the class 1 integron-integrase gene ( intI 1), but antibiotics indirectly influenced ARG profiles. The migration of ARGs in deep layer sediments was not related to the bacterial community and intI 1, but may be explained by antibiotic selective effects and ARG transformation.